The Effect Of Brand Image and Service Quality On Customer Satisfaction With Customer Perceived Value As A Mediating Variable - Leni Windayani; Survival; Yekti Intiyas Rahayu (Journal of Management Research and Studies, 2026)
This study aims to analyze the effect of Brand Image and Service Quality on Customer Satisfaction with Customer Perceived Value as a mediating variable at Gamma Grape Experience Educational Tourism, Pakis, Malang Regency. The study employed a quantitative approach with a causal research design. The population consisted of visitors of Gamma Grape Experience, while the sample was determined using purposive sampling techniques. Data were collected through questionnaires distributed to 105 respondents and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software.The results indicate that Brand Image has a positive and significant effect on Customer Satisfaction. Service Quality also has a positive and significant effect on Customer Satisfaction. Furthermore, Brand Image and Service Quality positively influence Customer Perceived Value. Customer Perceived Value significantly affects Customer Satisfaction. Mediation testing reveals that Customer Perceived Value partially mediates the relationship between Brand Image and Customer Satisfaction as well as the relationship between Service Quality and Customer Satisfaction. These findings suggest that enhancing visitors’ perceived value can strengthen the influence of Brand Image and Service Quality on Customer Satisfaction. Therefore, management should continuously improve service quality and maintain a strong brand image to increase customer satisfaction and encourage repeat visits.